Effect of Different Sources of Arsenic on Intake, Utilization of Nutrients and Growth Performance in Guinea Pigs - Mohanta, Ranjan K.; Garg, A. K.; Dass, R. S.; Behera, S. K. (Indian Journal of Animal Nutrition, 2018)
Twenty one adult guinea pigs (BW 583.4Â±10.1 g) were divided into3 groups of 7 animals each. Animals in group T1 were fed a control (basal) diet while arsenic (As) was added either as sodium arsenite or arsenic trioxide @ 50 mg As/kg in group T including a four days digestion trial. Dry matter intake was lower (P<0.05) and apparent absorption of As was higher (P<0.05) in As exposed groups. Growth rate and feed conversion efficiency were lower (P<0.05) in the arsenic exposed groups irrespective of the As compound. These results indicated that both compounds of arsenic (sodium arsenite and arsenic trioxide) given @ 50 mg/kg diet reduced feed intake, nutrient utilization and growth performance in guinea pigs.